Method for preparing dielectric microspheres by combining ultraviolet curing and microfluidic technology
By combining ultraviolet curing and microfluidic technology, barium titanate-based dielectric microspheres with uniform size and good dispersibility were prepared, solving the problem of microsphere preparation in the prior art. This method achieves high dielectric properties and sensitivity, and allows for the control of microsphere size and composition as needed.
Patent Information
- Application Number
- CN202511231237.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-30
- Publication Date
- 2026-01-02
AI Technical Summary
Existing technologies make it difficult to prepare barium titanate-based dielectric microspheres with uniform size, good dispersion, and high structural complexity.
A method combining ultraviolet light curing and microfluidic technology was used to prepare a barium titanate-based polymer ceramic precursor solution. The dispersed phase solution was sheared into droplets using a microfluidic chip and cured under ultraviolet light. Subsequently, pyrolysis and sintering were performed to prepare dielectric microspheres.
It achieves uniform size and high dielectric properties of dielectric microspheres, and has high sensitivity, allowing the size and composition of microspheres to be controlled according to actual needs.
Smart Images

Figure CN121248280A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of dielectric microspheres, and particularly relates to a preparation method of dielectric microspheres combining ultraviolet curing and microfluidic technology. BACKGROUND
[0002] Barium titanate-based dielectric microspheres have the advantages of high dielectric constant, low loss, excellent ferroelectric and piezoelectric effect, good thermal stability, etc. Barium titanate-based dielectric ceramic microspheres can be used as core dielectric layer materials in multilayer ceramic capacitors (MLCC); or used as thermal sensitive elements in positive temperature coefficient thermistors (PTCR) by using the resistivity mutation characteristics; or used in ultrasonic probes and vibration sensors by converting mechanical energy into electrical signals through piezoelectric effect; or used for drug release by virtue of high specific surface area and biocompatibility ([1] Zhang Peng, Wang Xin, Li Zhi. Research Progress of Piezoelectric Catalytic Properties of Barium Titanate-based Nanomaterials [J]. Chinese Journal of Composite Materials, 2023, 40(03): 1285-1299.). The application fields thereof cover consumer electronics, 5G communication, new energy vehicles, temperature sensing, energy storage, biomedical treatment, etc. At the same time, with the development of artificial intelligence, flexible electronic skin is also a hot spot. Barium titanate-based dielectric ceramic microspheres can be compounded with polymers to prepare flexible dielectric films, which are used in wearable sensors and flexible displays to achieve the application goals of high dielectricity, high sensitivity and high flexibility.
[0003] At present, a method for preparing dielectric microspheres with uniform size, good dispersibility and high structural complexity is urgently needed. SUMMARY
[0004] The present application provides a preparation method of dielectric microspheres combining ultraviolet curing and microfluidic technology, which comprises the following steps:
[0005] Preparation of barium titanate-based polymer ceramic precursor solution, and then adding appropriate amount of high molecular solubilizer, surfactant, photosensitive resin and photoinitiator to obtain a dispersed phase solution;
[0006] The dispersed phase solution and the continuous phase solution are respectively filled into different syringes, and then the dispersed phase solution is sheared into droplets at the cross-shaped neck by the continuous phase solution through a microfluidic chip;
[0007] The droplets are cured and shaped by ultraviolet light in a collecting liquid, and then the collecting liquid is removed by filtration, the residual collecting liquid is washed away with a cleaning reagent, and the cleaned microspheres are placed in a drying oven for curing treatment;
[0008] The cured microspheres are placed in a tube furnace for pyrolysis, calcination and sintering treatment in an inert atmosphere, and then transferred to a muffle furnace for sintering in an air atmosphere to obtain dielectric microspheres.
[0009] Further, a preparation method of a barium titanate-based polymer ceramic precursor solution is as follows:
[0010] Put the metal bar into the organic solvent, and after 2-4 hours of reaction at 50-80℃, add an appropriate amount of acetylacetone to obtain a bar-precursor solution;
[0011] Dissolve tetrabutyl titanate in the organic solvent, and add an appropriate amount of acetylacetone to mix uniformly to obtain a titanium-precursor solution;
[0012] Dissolve the dopant in the organic solvent, and add an appropriate amount of acetylacetone to mix uniformly to obtain a dopant-precursor solution;
[0013] Mix the above three solutions uniformly, and after 1-4 hours of reaction at 80-120℃, continue to react by dropwise adding an appropriate amount of deionized water. After the reaction is completed, remove part of the solvent by rotary evaporation to obtain a barium titanate-based polymer ceramic precursor solution;
[0014] The molar ratio of the metal bar, tetrabutyl titanate, dopant, and acetylacetone is 1:0.1-1:2. The organic solvent is one or more of isopropyl alcohol, 2-ethoxyethanol, n-propanol, ethanol, ethylene glycol methyl ether, toluene, and xylene. The dopant is one or more of n-propanol zirconium, isopropyl strontium, and 3-(methacryloyloxy)propyl trimethoxysilane. The molar ratio of the obtained solution to deionized water is 1:1-1:4.
[0015] Further, the types of the barium titanate-based polymer ceramic precursor include one or more of a barium titanate precursor, a barium zirconium titanate precursor, a barium strontium titanate precursor, and a barium silicate zirconate precursor.
[0016] Further, the high-molecular solubilizer is one or more of polyethylene glycol, polyvinylpyrrolidone, and polysorbate. The surfactant is one or more of Span-80, polysorbate-20, Plutonic F-68, and sodium dodecyl sulfate. The photosensitive resin is one or more of polyethylene glycol diacrylate, tripropyleneglycol diacrylate, and trimethylolpropane triacrylate. The photoinitiator is (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide.
[0017] Further, the dispersion phase solution is obtained by uniformly mixing the barium titanate-based polymer ceramic precursor solution with the high-molecular solubilizer, the surfactant, the photosensitive resin, and the photoinitiator. The mass fraction of the barium titanate-based polymer ceramic precursor in the dispersion phase solution is 19-82%. The mass fraction of the high-molecular solubilizer in the dispersion phase solution is 0-1.7%. The mass fraction of the photosensitive resin in the dispersion phase solution is 8-62%. The mass fraction of the surfactant in the dispersion phase solution is 0-15%. The mass fraction of the photoinitiator in the dispersion phase solution is 0.5-4.9%.
[0018] Further, the continuous phase solution is the same as the collection solution, and is one or more of dimethyl silicone oil, polyethylene glycol solution, glycerol, and ethylene glycol; preferably, the continuous phase solution and the collection solution can be dimethyl silicone oil.
[0019] Further, the injection pump parameters are that the continuous phase solution supply speed is 2-100 μL / min, the dispersed phase solution supply speed is 1-10 μL / min, and the interval time is 0-3 s.
[0020] Further, the high-temperature oven curing temperature is 50-200 °C.
[0021] Further, the pyrolysis and calcination temperature is 300-600 °C, the pyrolysis and calcination time is 1-12 hours, the sintering temperature in a tube furnace and a muffle furnace is 600-1300 °C, and the sintering time is 1-12 hours.
[0022] The application also provides a dielectric microsphere prepared by the preparation method of the dielectric microsphere combining ultraviolet light curing and microfluidic technology.
[0023] The application also provides application of the dielectric microsphere in the field of micro devices and sensors.
[0024] Compared with the prior art, the application has the following advantages and beneficial effects:
[0025] (1) The application provides a preparation method of a dielectric microsphere combining ultraviolet light curing and microfluidic technology; the dielectric microsphere prepared by the method has different barium titanate precursor solution configurations in the steps, and the components can be adjusted according to actual conditions.
[0026] (2) The size of the dielectric microsphere can be easily adjusted according to actual conditions.
[0027] (3) The dielectric microsphere has high dielectricity and high sensitivity.
[0028] (4) The dielectric microsphere prepared by the method provided by the application has uniform size. BRIEF DESCRIPTION OF DRAWINGS
[0029] Figure 1 It is a preparation flowchart of the dielectric microsphere.
[0030] Figure 2 It is a schematic diagram of droplet generation by a microfluidic process and ultraviolet light curing.
[0031] Figure 3 It is a SEM diagram of a single barium silicon zirconium titanate dielectric microsphere prepared in Example 2.
[0032] Figure 4 It is a SEM diagram of a plurality of barium silicon zirconium titanate dielectric microspheres prepared in Example 2.
[0033] Figure 5 XRD pattern of the barium zirconium titanate dielectric microspheres of Example 2.
[0034] Figure 6 SEM pattern of the barium titanate dielectric microspheres of Example 3.
[0035] Figure 7 Dielectric constant pattern of the barium titanate dielectric microspheres of Example 3.
[0036] Figure 8 SEM pattern of the barium zirconium titanate dielectric microspheres of Example 4. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. The described embodiments are only some of the embodiments of the present application, not all the embodiments.
[0038] According to the embodiments of the present application, the present application provides a preparation method of dielectric microspheres combining ultraviolet curing and microfluidic technology, the flow is as shown in Figure 1 The preparation method specifically includes the following steps:
[0039] A barium titanate-based precursor solution is prepared, and then an appropriate amount of a high-molecular solubilizer, a surfactant, a photosensitive resin and a photoinitiator are added to obtain a dispersed phase solution;
[0040] The dispersed phase solution and the continuous phase solution are respectively loaded into different syringes, and then the dispersed phase solution is sheared into droplets at the cross-shaped constriction by the continuous phase solution through a microfluidic chip;
[0041] The droplets are cured and shaped by ultraviolet light in a collection liquid, and then the collection liquid is removed by filtration, the residual collection liquid is washed away with a cleaning reagent, and the cleaned microspheres are placed in a drying oven for curing treatment;
[0042] The cured microspheres are placed in a tube furnace, pyrolyzed, calcined and sintered under an inert atmosphere, and then transferred to a muffle furnace for sintering under an air atmosphere to obtain dielectric microspheres.
[0043] According to the embodiments of the present application, the preparation method of the barium titanate-based precursor solution can include the following steps:
[0044] The metal barium is placed in an organic solvent, and after 2-4 hours of reaction at 50-80℃, an appropriate amount of acetylacetone is added to obtain a barium-precursor solution;
[0045] Tetrabutyl titanate is dissolved in an organic solvent, and an appropriate amount of acetylacetone is added and mixed uniformly to obtain a titanium-precursor solution;
[0046] The dopant is dissolved in an organic solvent, and an appropriate amount of acetylacetone is added and mixed uniformly to obtain a dopant precursor solution;
[0047] The three solutions are mixed uniformly, and after reaction at 80-120℃ for 1-4 hours, an appropriate amount of deionized water is added for continuous reaction. After the reaction is completed, part of the solvent is removed by rotary evaporation to obtain a barium titanate-based polymer ceramic precursor solution.
[0048] Example 1:
[0049] A dielectric microsphere material, the preparation method thereof comprising the following steps:
[0050] 1) Prepare a continuous phase solution and a dispersed phase solution:
[0051] Take 60 mL of polyethylene glycol solution as the continuous phase solution;
[0052] Put 9 grams of metallic barium into 135 grams of isopropyl alcohol and 135 grams of 2-ethoxyethanol, and after reaction at 80℃ for 4 hours, add 3 grams of acetylacetone to obtain a barium precursor solution;
[0053] Dissolve 17 grams of tetrabutyl titanate in 17 grams of isopropyl alcohol and 17 grams of 2-ethoxyethanol, and add 6 grams of acetylacetone and mix uniformly to obtain a titanium precursor solution;
[0054] Dissolve 6 grams of zirconium n-propylate in 18 grams of n-propyl alcohol and 6 grams of 2-ethoxyethanol, and add 1.5 grams of acetylacetone and mix uniformly to obtain a zirconium precursor solution;
[0055] Mix the barium precursor solution, the titanium precursor solution and the zirconium precursor solution uniformly, and after reaction at 120℃ for 2 hours, add 1.5 grams of deionized water for continuous reaction. After the reaction is completed, part of the solvent is removed by rotary evaporation to obtain a barium zirconium titanate precursor solution;
[0056] Take 3.5 grams of the barium zirconium titanate precursor solution and add 0.35 grams of sodium dodecyl sulfate, 0.35 grams of trimethylolpropane triacrylate and 0.1 grams of (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide and mix uniformly to obtain a dispersed phase solution.
[0057] 2) As shown in Figure 2 , the continuous phase solution and the dispersed phase solution are respectively sucked into different syringes, and the dispersed phase solution is sheared into droplets at the cross-shaped constriction by the continuous phase solution through a microfluidic chip. The supply speed of the continuous phase solution is 40 μL / min, the supply speed of the dispersed phase solution is 5 μL / min, and the interval is 1 s.
[0058] 3) Take the polyethylene glycol solution as the collection liquid, and when the microspheres are solidified and shaped in the collection liquid under the irradiation of ultraviolet light, the collection liquid is removed by filtration and the microspheres are washed with trichloroethylene. The obtained microspheres are placed in a high-temperature oven and heated to 50℃ for solidification for 8 hours.
[0059] 4) The cured microspheres are placed in a tube furnace for pyrolysis at 300℃ for 1 hour and sintering at 800℃ for 12 hours to obtain barium zirconate titanate carbon spheres with a diameter of 300 micrometers. The barium zirconate titanate carbon spheres are then transferred to a muffle furnace for sintering at the same temperature and time as in the tube furnace to obtain barium zirconate titanate dielectric microspheres with a diameter of 200 micrometers.
[0060] Example 2:
[0061] A dielectric microsphere material, the preparation method of which includes the following steps:
[0062] 1) Preparation of continuous phase solution and dispersed phase solution:
[0063] Take 60 mL of dimethyl silicone oil as the continuous phase solution;
[0064] Nine grams of metallic barium were placed in 135 grams of isopropanol and 135 grams of 2-ethoxyethanol, and reacted at 50°C for 2 hours. Then, 3 grams of acetylacetone were added to obtain a barium-precursor solution.
[0065] Dissolve 17 g of tetrabutyl titanate in 17 g of isopropanol and 17 g of 2-ethoxyethanol, add 6 g of acetylacetone and mix well to obtain a titanium-precursor solution.
[0066] Dissolve 6 g of zirconium propoxide in 18 g of n-propanol and 6 g of 2-ethoxyethanol, add 1.5 g of acetylacetone and mix well, then add a mixture of 1.5 g of 3-(methacryloyloxy)propyltrimethoxysilane and 3 g of isopropanol to obtain a zirconium silicon precursor solution.
[0067] The barium precursor, titanium precursor and silicon zirconium precursor solutions were mixed evenly and reacted at 120°C for 4 hours. Then, 1.5 g of deionized water was added dropwise to continue the reaction. After the reaction was completed, some of the solvent was removed by rotary evaporation to obtain the barium silicon zirconate titanate precursor solution.
[0068] Take 0.2 g of barium zirconate titanate precursor solution and add 0.15 g of Span-80, 0.52 g of trimethylolpropane triacrylate, 0.10 g of polyethylene glycol diacrylate and 0.04 g of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and mix well to obtain a dispersed phase solution.
[0069] 2) such as Figure 2 As shown, the continuous phase solution and the dispersed phase solution were drawn into separate syringes. Using a microfluidic chip, the dispersed phase solution was sheared into droplets by the continuous phase solution at the cross-shaped constriction. The continuous phase solution was supplied at a rate of 23 μL / min, and the dispersed phase solution at a rate of 4 μL / min, with no interval between injections.
[0070] 3) with dimethyl silicone oil as the collection liquid, when the microspheres are cured and shaped in the collection liquid by irradiation of ultraviolet light, the collection liquid is removed by filtration and the microspheres are washed with trichloroethylene, and the obtained microspheres are placed in a high-temperature oven, heated to 200°C and cured for 1 hour.
[0071] 4) The cured microspheres are placed in a tube furnace, pyrolyzed at 600°C for 2h and sintered at 1100°C for 4h to obtain barium silicon zirconium titanate carbon spheres with a diameter of 200 microns. The barium silicon zirconium titanate carbon spheres are transferred to a muffle furnace for sintering, and the sintering temperature and sintering time are the same as in the tube furnace to obtain barium silicon zirconium titanate dielectric microspheres with a diameter of 125 microns.
[0072] Example 3:
[0073] A dielectric microsphere material, the preparation method thereof comprising the following steps:
[0074] 1) Preparation of continuous phase solution and dispersed phase solution:
[0075] Take 60mL dimethyl silicone oil as the continuous phase solution;
[0076] Put 9 grams of metallic barium in 135 grams of isopropyl alcohol and 135 grams of 2-ethoxyethanol, add 3 grams of acetylacetone after reacting at 50°C for 3 hours to obtain a barium precursor solution;
[0077] Dissolve 12 grams of tetrabutyl titanate in 24 grams of isopropyl alcohol and 6 grams of ethanol, add 5.5 grams of acetylacetone and mix uniformly to obtain a titanium precursor solution.
[0078] Mix the titanium precursor and the titanium precursor solution uniformly, add 0.8 grams of deionized water dropwise after reacting at 100°C for 1 hour, and then spin evaporation to remove part of the solvent to obtain a barium titanate precursor solution;
[0079] Take 1 gram of the barium titanate precursor solution and add 0.53 grams of trimethylolpropane triacrylate, 0.10 grams of polyethylene glycol diacrylate and 0.04 grams of (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide and mix uniformly to obtain the dispersed phase solution.
[0080] 2) As shown in Figure 2 , the continuous phase solution and the dispersed phase solution are respectively sucked into different syringes, pass through the microfluidic chip, and the dispersed phase solution is sheared into droplets at the cross-shaped constriction by the continuous phase solution. The continuous phase solution is supplied at a speed of 70μL / min, and the dispersed phase solution is supplied at a speed of 4μL / min without interval.
[0081] 3) with dimethyl silicone oil as the collection liquid, when the microspheres are cured and shaped in the collection liquid by irradiation of ultraviolet light, the collection liquid is removed by filtration and the microspheres are washed with trichloroethylene, and the obtained microspheres are placed in a high-temperature oven, heated to 200°C and cured for 4 hours.
[0082] 4) The cured microspheres are placed in a tube furnace for pyrolysis at 500℃ for 12 hours and sintering at 1300℃ for 1 hour to obtain barium zirconate titanate carbon spheres with a diameter of 300 micrometers. The barium zirconate titanate carbon spheres are then transferred to a muffle furnace for sintering at the same temperature and time as in the tube furnace to obtain barium zirconate titanate dielectric microspheres with a diameter of 200 micrometers.
[0083] Example 4:
[0084] A dielectric microsphere material, the preparation method of which includes the following steps:
[0085] 1) Preparation of continuous phase solution and dispersed phase solution:
[0086] Take 60 mL of ethylene glycol as the continuous phase solution;
[0087] 3 grams of metallic barium were placed in 45 grams of isopropanol and 45 grams of xylene, and reacted at 60°C for 4 hours. Then 1 gram of acetylacetone was added to obtain a barium precursor solution.
[0088] Dissolve 7 g of tetrabutyl titanate in 7 g of isopropanol and 7 g of xylene, add 2.5 g of acetylacetone and mix well to obtain a titanium precursor solution.
[0089] The barium precursor, titanium precursor and zirconium precursor solutions were mixed evenly and reacted at 80°C for 1 hour. Then, 1.5 g of deionized water was added dropwise to continue the reaction. After the reaction was completed, some of the solvent was removed by rotary evaporation to obtain the barium zirconate titanate precursor solution.
[0090] Take 2 g of barium zirconate titanate precursor solution and add 0.02 g of polysorbate, 0.16 g of polysorbate-20, 1.75 g of tripropylene glycol diacrylate and 0.02 g of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and mix well to obtain a dispersed phase solution.
[0091] 2) such as Figure 2 As shown, the continuous phase solution and the dispersed phase solution were drawn into separate syringes. Using a microfluidic chip, the dispersed phase solution was sheared into droplets by the continuous phase solution at the cross-shaped constriction. The continuous phase solution was supplied at a rate of 2 μL / min, and the dispersed phase solution at a rate of 1 μL / min, with no interval between injections.
[0092] 3) Using ethylene glycol as the collecting liquid, after the microspheres are solidified and shaped by ultraviolet light irradiation in the collecting liquid, the collecting liquid is filtered out and the microspheres are washed with trichloroethylene. The resulting microspheres are placed in a high-temperature oven and heated to 120°C for 4 hours to solidify.
[0093] 4) The cured microspheres were placed in a tube furnace for pyrolysis at 300℃ for 8 hours and sintering at 600℃ for 4 hours to obtain barium zirconate titanate carbon spheres with a diameter of 250 micrometers. The barium zirconate titanate carbon spheres were then transferred to a muffle furnace for sintering at the same temperature and time as in the tube furnace to obtain barium zirconate titanate dielectric microspheres with a diameter of 150 micrometers.
[0094] Example 5:
[0095] A dielectric microsphere material, the preparation method of which includes the following steps:
[0096] 1) Preparation of continuous phase solution and dispersed phase solution:
[0097] Take 60 mL of dimethyl silicone oil as the continuous phase solution;
[0098] Five grams of metallic barium were placed in 75 grams of isopropanol and 75 grams of ethylene glycol methyl ether, and reacted at 80°C for 2 hours. Then, 2 grams of acetylacetone were added to obtain a barium precursor solution.
[0099] Dissolve 12 g of tetrabutyl titanate in 12 g of isopropanol and 12 g of ethylene glycol methyl ether, add 4 g of acetylacetone and mix well to obtain a titanium precursor solution.
[0100] Dissolve 6 g of zirconium n-propoxide in 18 g of n-propanol and 6 g of 2-ethoxyethanol, add 1.5 g of acetylacetone and mix well to obtain a zirconium precursor solution.
[0101] The barium precursor, titanium precursor and zirconium precursor solutions were mixed evenly and reacted at 80°C for 1 hour. Then, 1.5 g of deionized water was added dropwise to continue the reaction. After the reaction was completed, some of the solvent was removed by rotary evaporation to obtain the barium zirconate titanate precursor solution.
[0102] Take 3 g of barium zirconate titanate precursor solution and add 0.02 g of polyvinylpyrrolidone, 0.05 g of Plutonic F-68, 0.6 g of trimethylolpropane triacrylate and 0.04 g of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and mix well to obtain a dispersed phase solution.
[0103] 2) such as Figure 2 As shown, the continuous phase solution and the dispersed phase solution were drawn into different syringes. Using a microfluidic chip, the dispersed phase solution was sheared into droplets by the continuous phase solution at the cross-shaped constriction. The continuous phase solution was supplied at a rate of 50 μL / min, and the dispersed phase solution at a rate of 10 μL / min, with a 3-second interval between each injection.
[0104] 3) Using dimethyl silicone oil as the collecting liquid, after the microspheres are cured and shaped by ultraviolet light in the collecting liquid, the collecting liquid is filtered out and the microspheres are washed with trichloroethylene. The obtained microspheres are placed in a high-temperature oven and heated to 200℃ for 1 hour to cure.
[0105] 4) The cured microspheres are placed in a tube furnace for pyrolysis at 500℃ for 4 hours and sintering at 1300℃ for 1 hour to obtain barium zirconate carbon spheres with a diameter of 300 micrometers. The barium zirconate carbon spheres are then transferred to a muffle furnace for sintering at the same temperature and time as in the tube furnace to obtain barium zirconate dielectric microspheres with a diameter of 200 micrometers.
[0106] Example 6:
[0107] A dielectric microsphere material, the preparation method of which includes the following steps:
[0108] 1) Preparation of continuous phase solution and dispersed phase solution:
[0109] Prepare a continuous phase solution of 60 mL glycerol.
[0110] Nine grams of metallic barium were placed in 135 grams of isopropanol and 135 grams of 2-ethoxyethanol, and reacted at 50°C for 2 hours. Then, 3 grams of acetylacetone were added to obtain a barium precursor solution.
[0111] Dissolve 17 g of tetrabutyl titanate in 17 g of isopropanol and 17 g of 2-ethoxyethanol, add 6 g of acetylacetone and mix well to obtain a titanium precursor solution.
[0112] Dissolve 6 g of zirconium propoxide in 18 g of n-propanol and 6 g of 2-ethoxyethanol, add 1.5 g of acetylacetone and mix well, then add a mixture of 1.5 g of 3-(methacryloyloxy)propyltrimethoxysilane and 3 g of isopropanol to obtain a zirconium silicon precursor solution.
[0113] The barium precursor, titanium precursor and silicon zirconium precursor solutions were mixed evenly and reacted at 80°C for 1 hour. Then, 1.5 g of deionized water was added dropwise to continue the reaction. After the reaction was completed, some of the solvent was removed by rotary evaporation to obtain the barium silicon zirconate titanate precursor solution.
[0114] Take 0.5 g of barium zirconate titanate precursor solution and add 0.02 g of polyethylene glycol, 0.65 g of tripropylene glycol diacrylate and 0.06 g of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide. Mix well to obtain a dispersed phase solution.
[0115] 2) such as Figure 2 As shown, the continuous phase solution and the dispersed phase solution were drawn into different syringes. Using a microfluidic chip, the dispersed phase solution was sheared into droplets by the continuous phase solution at the cross-shaped constriction. The continuous phase solution was supplied at a rate of 100 μL / min, and the dispersed phase solution at a rate of 8 μL / min, with a 1-second interval.
[0116] 3) using glycerol as the collecting liquid, when the microspheres are cured and shaped in the collecting liquid by irradiation of ultraviolet light, the collecting liquid is removed by filtration and the microspheres are cleaned with trichloroethylene, and the obtained microspheres are placed in a high-temperature oven, heated to 200°C and cured for 1 hour.
[0117] 4) the cured microspheres are placed in a tube furnace, pyrolyzed at 500°C for 2h, sintered at 1200°C for 1h, to obtain barium silicon zirconium titanate carbon spheres with a diameter of 300 microns. The barium silicon zirconium titanate carbon spheres are transferred to a muffle furnace for sintering, and the sintering temperature and sintering time are the same as in the tube furnace, to obtain barium silicon zirconium titanate dielectric microspheres with a diameter of 200 microns.
[0118] Figure 3 、 Figure 6 、 Figure 8 The SEM images of the single dielectric microspheres prepared in Examples 2, 3 and 4 are shown, and the size of the dielectric microspheres prepared by the method provided by the application can be adjusted according to actual conditions.
[0119] Figure 4 The SEM images of the plurality of barium silicon zirconium titanate dielectric microspheres prepared in Example 2 are shown, and the dielectric microspheres prepared by the preparation method provided by the application have uniform sizes.
[0120] High dielectricity is a key indicator of sensitivity, Figure 7 The dielectric constant diagram of the barium titanate dielectric microspheres prepared in Example 3 is shown, and the dielectric constant of the dielectric microspheres can reach more than 6000, indicating that they have high dielectricity.
[0121] The application provides a preparation method of dielectric microspheres combining ultraviolet curing and microfluidic technology; the dielectric microspheres prepared by the method can be configured to use different barium titanate-based precursor solutions in the steps, and the components thereof can be adjusted according to actual conditions;
[0122] The size of the dielectric microspheres can be easily adjusted according to actual conditions;
[0123] Such dielectric microspheres have high dielectricity and high sensitivity;
[0124] The dielectric microspheres prepared by the method provided by the application have uniform sizes.
[0125] The above examples are preferred embodiments of the application, but the embodiments of the application are not limited by the above examples, and any changes, modifications, substitutions, combinations and simplifications made without departing from the spirit and principles of the application shall be equivalent replacement methods, and all shall be included in the protection scope of the application.
Claims
1. A method for preparing dielectric microspheres combining ultraviolet light curing and microfluidic technology, characterized in that, Includes the following steps: A barium titanate-based precursor solution was prepared, and then an appropriate amount of polymeric solubilizer, surfactant, photosensitive resin and photoinitiator were added to obtain a dispersed phase solution. The dispersed phase solution and the continuous phase solution were loaded into different syringes. Through the microfluidic chip, the dispersed phase solution was sheared into droplets by the continuous phase solution at the cross-shaped constriction. The droplets are solidified and shaped by ultraviolet light in the collection liquid. After filtering to remove the collection liquid, the residual collection liquid is washed away with a cleaning reagent. The cleaned microspheres are then placed in a drying oven for solidification. The solidified microspheres were placed in a tube furnace and subjected to pyrolysis, calcination and sintering in an inert atmosphere. They were then transferred to a muffle furnace and sintered in an air atmosphere to obtain dielectric microspheres.
2. The method for preparing dielectric microspheres combining ultraviolet light curing and microfluidic technology according to claim 1, characterized in that, The method for preparing the barium titanate-based precursor solution includes the following steps: Barium metal is placed in an organic solvent and reacted at 50-80℃ for 2-4 hours. Then, an appropriate amount of acetylacetone is added to obtain a barium-precursor solution. Tetrabutyl titanate was dissolved in an organic solvent, and an appropriate amount of acetylacetone was added and mixed evenly to obtain a titanium-precursor solution. The dopant is dissolved in an organic solvent, and an appropriate amount of acetylacetone is added and mixed evenly to obtain a dopant precursor solution. Mix the three solutions thoroughly and react at 80-120℃ for 1-4 hours. Then add an appropriate amount of deionized water to continue the reaction. After the reaction is complete, remove some of the solvent by rotary evaporation to obtain the barium titanate-based polymer ceramic precursor solution.
3. The method for preparing dielectric microspheres combining ultraviolet light curing and microfluidic technology according to claim 1, characterized in that, The types of barium titanate-based polymer ceramic precursors are one or more of barium titanate precursors, barium zirconate titanate precursors, barium silicon zirconate titanate precursors, and barium strontium titanate precursors.
4. The method for preparing dielectric microspheres combining ultraviolet curing and microfluidic technology according to claim 1, characterized in that, The polymeric solubilizer is one or more of polyethylene glycol, polyvinylpyrrolidone, and polysorbates; the surfactant is one or more of Span-80, polysorbate-20, Plutonic F-68, and sodium dodecyl sulfate; the photosensitive resin is one or more of polyethylene glycol diacrylate, tripropylene glycol diacrylate, and trimethylolpropane triacrylate; and the photoinitiator is (2,4,6-trimethylbenzoyl)diphenylphosphine oxide.
5. The method for preparing dielectric microspheres combining ultraviolet curing and microfluidic technology according to claim 1, characterized in that, A dispersed phase solution is obtained by uniformly mixing a barium titanate-based polymer ceramic precursor solution with a polymeric solubilizer, a surfactant, a photosensitive resin, and a photoinitiator. The mass fraction of the barium titanate-based polymer ceramic precursor solution in the dispersed phase solution is 19–82%, the mass fraction of the polymeric solubilizer is 0–1.7%, the mass fraction of the photosensitive resin is 8–62%, the mass fraction of the surfactant is 0%–15%, and the mass fraction of the photoinitiator is 0.5%–4.9%.
6. The method for preparing dielectric microspheres combining ultraviolet light curing and microfluidic technology according to claim 1, characterized in that, The continuous phase solution is the same as the collecting solution, and is one or more of dimethyl silicone oil, polyethylene glycol solution, glycerol, and ethylene glycol.
7. The method for preparing dielectric microspheres combining ultraviolet curing and microfluidic technology according to claim 1, characterized in that, The syringe pump parameters are as follows: continuous phase solution supply rate of 2–100 μL / min, dispersed phase solution supply rate of 1–10 μL / min, and interval time of 0–3 s.
8. The method for preparing dielectric microspheres combining ultraviolet curing and microfluidic technology according to claim 1, characterized in that, The curing temperature in the high-temperature oven is 50–200℃, and the curing time is 1–8 hours.
9. The method for preparing dielectric microspheres combining ultraviolet curing and microfluidic technology according to claim 1, characterized in that, The pyrolysis and calcination temperatures are 300–600℃, and the pyrolysis and calcination times are 1–12 hours; the sintering temperatures in tube furnaces and muffle furnaces are 600–1300℃, and the sintering times are 1–12 hours.
10. A dielectric microsphere, characterized in that, It is prepared according to the preparation method according to claims 1 to 9.
Citation Information
Patent Citations
Batch production method of monodisperse tetragonal barium titanate hollow microspheres
CN113603134A
Preparation method of tetragonal-phase barium titanate ceramic powder with antibacterial property
CN113716954A
Preparation method of nanocrystalline metal microspheres for 3D printing
CN114653961A
Method for preparing porous magnetic / temperature-sensitive microspheres through microfluidics as well as product and application of porous magnetic / temperature-sensitive microspheres
CN115055126A
Method for preparing bionic compound eye based on microfluidic technology
CN115624931A
Cited By
Method for preparing ceramic microspheres by combining photocuring ceramic precursor and microfluidic technology
CN121360537A
